Usaha Pembaharuan Pendidikan Islam di Mesir: Jamaluddin Al-Afghani dan Muhammad Abduh - hairul amin hairul; Djeprin E. Hulawa Djeprin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This article comprehensively examines the dynamics of Islamic educational reform in Egypt during the nineteenth and early twentieth centuries, focusing on the thoughts and contributions of Sayyid Jamal al-Din al-Afghani and Muhammad Abduh. During this period, Egypt faced an identity crisis caused by internal intellectual stagnation and the growing influence of Western imperialism. This study employs a library research method with a historical-philosophical approach to analyze how both figures responded to these challenges. Primary sources include Al-Urwah al-Wuthqa and Risalat al-Tawhid, while secondary sources consist of scholarly books, journal articles, theses, and dissertations. Data were collected from various publications and analyzed through historical research stages, namely heuristics, source criticism, interpretation, and historiography. The findings reveal that al-Afghani and Abduh played pivotal roles in reforming Islamic education in Egypt. Their reforms emphasized the integration of modern sciences, the purification of Islamic teachings, and the revitalization of ijtihad. These ideas encouraged a shift from rote learning to a more critical and rational educational approach. Despite encountering resistance, their reforms laid the foundation for the modernization of Islamic education and influenced reform movements across the Muslim world, including Indonesia. This study is limited by its reliance on library-based research and does not empirically examine the implementation of these reform ideas in contemporary educational practices. Therefore, future studies are recommended to adopt comparative and multidisciplinary approaches to explore the relevance and application of these reformist ideas in modern Islamic education.